Arthropod biodiversity loss from nitrogen deposition is buffered by natural and semi-natural habitats. - Shunxiang Fan; Tim Newbold; Jan C Axmacher; Charlotte L Outhwaite; Yi Zou; Zhenrong Yu; Yunhui Liu (PLoS Biology)
Nitrogen (N) deposition is known to strongly modify biogeochemical cycles and trophic interactions, in turn altering ecosystem functioning and plant diversity around the globe. However, our understanding of N deposition effects on arthropod diversity remains limited. Here, we investigate how N deposition impacts the diversity of arthropods by combining biodiversity data from the PREDICTS database with data on global N deposition and land cover using mixed-effects models. We then explore the potential for semi-natural and natural habitats ('SNH') to buffer against potential N deposition-linked biodiversity losses. N deposition has a negative effect on arthropod biodiversity. Both, species richness and abundance are significantly reduced in areas of high levels of N deposition when compared to areas of low N deposition, with responses varying across different land-use types. The strongest negative effects of N deposition on arthropod diversity were observed in locations where the local land use entails the least anthropogenic modification. At the same time, with the exception of cropland-dominated landscapes, increases in the amount of SNH in the surrounding landscape reduced arthropod biodiversity losses associated with N deposition. We conclude that SNH can play an important role in mitigating the negative effects of N deposition on arthropod diversity, with the conservation and creation of these habitats promoting arthropod diversity even under high levels of N deposition.